Prevalence of overweight and obesity and associated risk factors among adult residents of northwest China: a cross-sectional study - Xiao-Mei Li; Yi-Ning Yang; Ning Song; Fen Liu; Min Han; Qiang Zhao; Qian Zhao; Hui Zhai; Xiang-Mei Li; Guo-Li Du (BMJ Open)
Objective Overweight and obesity have been shown to be related to multiple chronic conditions, leading to a heavy economic burden on society throughout the world. This study aims to estimate the prevalence of overweight and obesity and determine potential influencing factors among adults in Xinjiang, northwest China.Design A community-based observational study.Setting The First Affiliated Hospital of Xinjiang Medical University.Methods In total, 14 618 adult participants (7799 males; 6819 females) aged over 35 years were recruited from the Cardiovascular Risk Survey conducted in 2010. Data were obtained from face-to-face interviews and physical examinations. The sample was used to estimate the prevalence of overweight (body mass index (BMI) 24–28 kg/m2) and obesity (BMI ≥28 kg/m2) in Xinjiang Province. Influencing factors were analysed based on statistical methods.Results In Xinjiang Province, the overall prevalence of overweight was 36.5% (male 40.1%; female 33.4%), and the prevalence of obesity was 26.5% (male 27.2%; female 25.8%). The prevalence of both overweight and obesity were higher in women than in men (p<0.001). The main influencing factors for overweight and obesity were sex, age, race, marital status, education level, occupation, smoking, drinking, hypertension, diabetes and dyslipidaemia (p<0.05).Conclusions This study estimated that the prevalence of overweight and obesity among adult residents of Xinjiang Province, northwest China, was high. These data suggest that efforts related to the prevention and control of overweight and obesity should be a public health priority in northwest China.